The Quadruple Bottom Line: Tenant Views of Corporate Responsibility in Green Office Buildings - Robert A. Simons; Spenser Robinson; Eunkyu Lee; Albert Bragg (Journal of Sustainable Real Estate, 2017)
This research expands the traditional triple bottom line (people, profit, and planet) by splitting profit based on benefits from resource savings or productivity enhancements. In the context of corporate real estate, the suggested quadruple bottom line (PPPP) is defined as general environmental goals (planet), employees' productivity (people), the tenant firm's profitability (profit T), and landlord's profit (profit L). Tenants' perspectives on specific sustainability categories and the relative importance of PPPP are examined through a survey of over 700 tenants in U.S. office buildings. The findings suggest that different ways of evaluating the direction of profit is warranted, because tenants' attitudes toward profit diverge significantly when landlord profit and tenant profit are considered separately based on lease structure. The results also suggest that while planet, or resource conservation, is a major priority for tenant respondents, detailed analysis of sustainability components shows that people, a proxy for occupant well-being and productivity gains, are the highest priority. This is of particular importance in sustainable real estate as new products and developments are considered.